The Baptist story from English sect to global movement - Chute, Anthony L.; Finn, Nathan A. 1979-; Haykin, Michael A. G. 1953- (Nashville, Tennessee B & H Academic, 2015)
The Baptist Story is a narrative history spanning more than four centuries of a diverse group of people living among distinct cultures on separate continents while finding their identity in Christ and expressing their faith as Baptists. Baptist historians Anthony Chute, Nathan Finn, and Michael Haykin highlight the Baptist transition from a despised sect to a movement of global influence. Each chapter includes stories of people who made this history so fascinating. Although the emphasis is on the English-speaking world, The Baptist Story integrates stories of non-English-speaking Baptists, ethnic minorities, women, and minority theological traditions, all within the context of historic, orthodox Christianity. Written with an irenic tone and illustrated with images in every chapter, The Baptist Story is ideally suited for graduate and undergraduate courses, as well as group study in the local church. - Back cover
Introduction -- Section one : Baptists in the seventeenth and eighteenth centuries. Baptist beginnings -- Living under the cross -- The age of reason and revival -- Renewal and advance -- Section two : Baptists in the nineteenth century. Baptists and the world before them -- Progress and setbacks -- Expansion and adaptation -- Transitions and trends -- Section three : Baptists in the twentieth and twenty-first centuries. The early twentieth century -- Tension and expansion -- Controversies in a changing world -- Developments into the twenty-first century -- Section four : Baptist beliefs. Identity and distinctives
Includes bibliographical reference and indexes
Keywords: Baptists -- History; Anabaptists -- History; Separate Baptists -- History; Baptists, Black -- History